Perancangan dan Implementasi Sistem Sewa Mobil untuk Kendaraan Operasional - Putri, Elfara Nadiva; Harahap, Adriansyah Putra (Universitas Islam Negeri Sumatera Utara, 2024)
PT Indonesia Comnets Plus (ICON+) Regional West Java SBU requires improved efficiency in managing operational vehicle rentals, which was previously done manually. This study aims to design and implement a web-based vehicle rental system using the Laravel framework to simplify the rental process and data management. The system is designed based on 107 functional requirements and 15 non-functional requirements, developed using the agile scrum approach, which includes five stages: 1) sprint planning, 2) system development, 3) testing, 4) sprint review, and 5) deployment. The testing was conducted using Blackbox Testing and User Acceptance Testing (UAT). The results of the study show that the implemented system successfully enhances operational efficiency, minimizes the risk of errors, and facilitates monitoring vehicle usage through an integrated dashboard. The UAT results indicate that the system falls under the